Evaluation of Patients with Malignant otitis external Treated in Our Clinic - Dedeoğlu, Serkan; Ayral, Muhammed; Toprak, Serdar Ferit (International Journal of Innovative Research in Medical Science, 2022)
Background: Malignant otitis is a disease that occurs after an external ear canal infection and spreads towards the skull base. It is a complex condition to treat because it shows clinical differences between patients and different responses to treatment. Malignant otitis We investigated the epidemiology and treatment management of patients hospitalized with external diagnoses. Material and Methods: This study was carried out between January 2014 and May 2020 in Dicle University ENT Clinic, which was treated and treated with malignancy. Otitis was designed as a retrospective study that analyzed 22 patients diagnosed with externa. Results: All patients in the study had diabetes. He had diabetes mellitus. Pseudomonas aeruginosa was grown in the culture of 17 of the patients. Although otalgia was the most common symptom, discharge from the external ear canal and development of edema and obstruction were also observed. Two of our patients were hospitalized again as a result of recurrence. Conclusion: Malignant disease in the practice of otolaryngology otitis It is a complex disease to treat due to the lack of a standard treatment protocol for externa. Therefore, early diagnosis and early initiation of treatment reduce the patients' hospital stay. Early diagnosis and treatment are the most critical factors in reducing mortality and morbidity.